2021
DOI: 10.34172/jrhs.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Factors for the Primary Prevention of Breast Cancer: A Meta-Analysis of Prospective Cohort Studies

Abstract: Background: This report provided the effect of 15 preventable factors on the risk of breast cancer incidence. Study design: A systematic review and meta-analysis. Methods: A detailed research was conducted on PubMed, Web of Science, and Scopus databases in January 2020. Reference lists were also screened. Prospective cohort studies addressing the associations between breast cancer and 15 factors were analyzed. Between-study heterogeneity was investigated using the χ2 , τ2 , and I2 statistics. The probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…It was identified that a history of ever breastfeeding decreased the odds of developing BC by 72% (AOR = 0.28, 95% CI: 0.15–0.42) which is supported by findings of previous meta-analyses done in other countries [ 25 , 26 ]. Breastfeeding reduces BC risk biologically through lower levels of systemic estrogen and progesterone levels during breastfeeding and the excretion of estrogen and carcinogens from the breast ducts [ 21 ].…”
Section: Discussionsupporting
confidence: 78%
“…It was identified that a history of ever breastfeeding decreased the odds of developing BC by 72% (AOR = 0.28, 95% CI: 0.15–0.42) which is supported by findings of previous meta-analyses done in other countries [ 25 , 26 ]. Breastfeeding reduces BC risk biologically through lower levels of systemic estrogen and progesterone levels during breastfeeding and the excretion of estrogen and carcinogens from the breast ducts [ 21 ].…”
Section: Discussionsupporting
confidence: 78%
“…We also observed that the decrease in both Sfrp1 and Esr1 expression following E2 treatment was associated with a lobulo-alveolar phenotype in organoids obtained from nulliparous mice only. Interestingly, nulliparous women have a majority of type 1 lobules (>12 acini), which are more positive to ERα and PR than type 3 lobules (>80 acini), while parous women have more type 3 lobules, expressing less ERα and PR than type 1 lobules, which is concordant with the fact that organoids obtained from nulliparous mice expressed more Esr1 than those obtained from multiparous mice [ 12 , 13 , 14 , 15 , 49 , 50 ]. In addition, virgin mice depleted of Sfrp1 developed branched mammary glands, similar to pregnant mice in vivo, corroborating that the decrease in Sfrp1 expression by E2 treatment in organoids obtained from nulliparous mice increased organoid luminal organization ex vivo [ 22 ].…”
Section: Discussionsupporting
confidence: 59%
“…A balanced diet including extra virgin olive oil (LoE2b/B/AGO+), nuts (LoE 2b/B/AGO+) (>10 g/die), reduced consumption of fat (LoE2a/B/AGO+), and reduced consumption of red meat (LoE2b/C/AGO+) may decrease the incidence of breast cancer. For other factors such as supplementation of vitamin D3 (LoE1b/B/AGO+/−), vegetarian or vegan diet (LoE2b/C/AGO+/−), vegetables and fruits (LoE2a/B/AGO+/−), dairy products or phytoestrogens (LoE2a/B/AGO+/−), the data are contradictory regarding the reduction of breast cancer incidence [4, 5]. However, it should be considered that prospective randomized trials to investigate the impact of nutrition aspects on breast cancer risk are almost impossible to conduct.…”
Section: Options For Primary Prevention and Lifestyle Factorsmentioning
confidence: 99%